Interaction of Saccharomyces cerevisiae and Lactococcus lactis in the fermentation and quality of artisanal cachaça - Carvalho, Fernanda Paula; Duarte, Whasley Ferreira; Dias, Disney Ribeiro; Piccoli, Roberta Hilsdorf; Schwan, Rosane Freitas (Acta Scientiarum. Agronomy, 2014)
Lactococcus lactis and Saccharomyces cerevisiae in co-culture were evaluated during sugar cane fermentantion for cachaça production. The inocula containing L. lactis UFLA CA 312 and S. cerevisiae UFLA CA 11 were used in the population of approximately 105 CFU mL-1 and 108 CFU mL-1, respectively. The sugar cane medium plus 1% of yeast extract (SCM) was efficient for growth of L. lactis UFLA CA 312 and S. cerevisiae UFLA CA 11 (letter ‘b’-Tukey test). In flasks and vats fermentation the growth of UFLA CA 11 was not negatively influenced by L. lactis UFLA CA 312. However, after 19 hours of fermentation, bacterial population showed a slight decrease. Considering parameters higher alcohols and aldehydes, cachaça produced by pure culture of S. cerevisiae was similar to cachaça produced by mixed culture. Cachaça produced by mixed culture showed high values of volatile acidity (letter ‘b’-Tukey test) being characterized by this parameters in the principal component analysis. High percentage of acceptance (81.10%) for the attribute aroma was observed in samples from cachaça produced by mixed culture.